The Effect of Perceived Organizational Support and Organizational Commitment to Organizational Citizenship Behavior Nurse Dr. Tadjuddin Chalid - et. al, Della Aprilani , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of organizational support in the relationship between the organization and employees is the way in which work attitudes and employee behavior are influenced by the relationship between employees and the organization. This study aims to analyze the effect of perceived organizational support on organizational citizenship behavior of nurses, analyze the effect of perceived organizational support on nurses' organizational commitment, analyze the effect of organizational commitment on organizational citizenship behavior of nurses, analyze the direct and indirect effects of perceived organizational support on organizational citizenship behavior through commitment. organizational nurse Dr. Tadjuddin Chalid Makassar. This type of research is a quantitative study using an observational study with a cross sectional study design. Sampling using total sampling so that the sample in this study were nurses at Dr. Tadjuddin Chalid Makassar, totaling 106 respondents. The results showed that perceived organizational support is related to organizational commitment of nurses, perceived organizational support is related to organizational citizenship behavior of nurses, organizational commitment is related to organizational citizenship behavior of nurses, variables perceived organizational support and organizational commitment have a direct effect on organizational citizenship behavior of nurses, and there is no influence. The direct variable perceived organizational support for organizational citizenship behavior through organizational commitment of nurses at Dr. Tadjuddin Chalid Makassar. Therefore, management is expected to pay attention to employee engagement and employee expectations by providing allowances, providing opportunities to continue higher education, promotion, awarding exemplary nurses and participating in organizational policy making.